Development of learning tools based on realistic mathematics approach that oriented to high school students' mathematical generalization ability - Hayuningrat, Silfia; Rosnawati, Raden (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
Generalization ability need to be encouraged in learning mathematics, students with generalization abilities can expand and transfer knowledge to practical knowledge. This research aims to develop learning material based on realistic mathematisc approach that oriented to generalization ability. The learning materials'developed is lesson plans and student worksheets. This is research and development with an ADDIE model. The instruments used in this study were the evaluation sheets, response questionnaire for teachers and students and tests of mathematical generalization ability. The data analysis technique used was descriptive qualitative and quantitative. The design of the learning materials focuses on aspects of the mathematical generalization ability of high school students by presenting real problems. Student activities are designed to solve real issues related to pattern analysis, focus on student contributions to find conjectures, and design interactions so students can proceed to the abstraction stage using concept linkages. So students can make conclusions regarding the given concept in response to such issues. The results show that the validity qualifications of lesson plans and student worksheets are good and very good, the practical qulifications are very good. The learning materials comply with effective based on completeness tests of generalization ability of 82.26 with good qualifications